Virtuell 3D-modellering som verktyg - Abrahamsson, Kristina (2013)
3D modeling is a common tool in landscape architecture. Today, there have been new ways in which virtual 3D models are successful tools in the dialogue with the public. These new methods involve children and young people who are groups that is hard to reach and engage in citizen dialogues. The purpose of this work was to investigate how a virtual 3D model works in the landscape architect’s communication with the public through the project Gruvstadsparken in Kiruna. Through workshops, I wanted to communicate Gruvstadsparken to get ideas from participants on how the park can be used and be revisited. The question for my work was: How can I with a virtual 3D-model of a place, receive an increased understanding of 3D-modeling as a tool in the communication process with the public? In Kiruna, a major transformation of the city is going on due to the development of the mine. Kiruna municipality and LKAB have decided to build a temporary park called Gruvstadsparken (Mining City Park). The idea is that the park should be a smooth transition between the mine and the town where no one has to live next to the growing mining area. Through the project Kiruna municipality and LKAB want to create a good communication with the residents of Kiruna and the idea is to engage the public in the development of Gruvstadsparken. In my work three school classes has studied the plans for the park through a virtual 3D model during workshops, with a final survey. The 3D model was based on a complete design proposal for Gruvstadsparken. In my work, communication was a multi-process where young people would feel that they were involved. Public participation in the development of communities promotes social sustainability as evidenced by the Rio Declaration, Agenda 21 and the Habitat Agenda. The students' reaction to the design proposal of Gruvstadsparken was that it was exciting and cool, but the question came quickly how the park should be used. Students designed their own ideas and suggestions for how the park could be used through the 3D ...